The Effect Of Promotion, Service Quality And Administration Of Voting Interest Sharia People's Business Credit In PT. Pegadaian Syariah - Manyang, Cut Merah; Usman, Ismuadi; Tarigan, Ismail Rasyid Ridla (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Influence of Promotion Factors, Service Quality and Administration on Customer Interest in Choosing Sharia People's Business Credit (KUR) Products at PT. Pegadaian Syariah Banda Aceh City. The purpose of this study is to analyze the influence of these factors on customer interest in using the People's Business Credit (KUR) product. This study employed a quantitative method, utilizing primary data sources and a questionnaire-based data collection technique distributed through simple random sampling, targeting active customers who have chosen the People's Business Credit (Kredit Usaha Rakyat, KUR) products at PT. Pegadaian Syariah, Banda Aceh. The sample consisted of 85 respondents, and multiple linear regression analysis was used to test the hypotheses. The results of the multiple linear regression analysis assisted by SPSS, found that partially the service quality variable has a significant positive effect on customer interest, while the promotion and administration variables do not affect customer interest. However, the three independent variables simultaneously have a positive effect on Customer Interest in Choosing Sharia People's Business Credit (KUR) Products at PT. Pegadaian Syariah Banda Aceh City.